Cardiolens: Remote Physiological Monitoring in a Mixed Reality Environment - McDuff, Daniel; Hurter, Christophe (ACM SIGGRAPH 2017 Emerging Technologies, 2017)
Numerous vital signs can be captured through the measurement of blood flow; however, these signals are not visible to the unaided eye and measurement traditionally requires customized contact sensors. We present Cardiolens - a mixed reality application that enables real-time hands-free measurement and visualization of blood flow and vital signs. The system combines a front-facing camera, remote imaging photoplethysmography software and a heads-up display allowing users to view the physiological state of a person simply by looking at them. Cardiolens provides the wearer with a new way to understand physiology and has applications in healthcare and effective computing.